POLA AKTIVITAS TAPIR (Tapirus indicus Desmarest 1819) DI HUTAN KALAWEIT SUPAYANG, KABUPATEN SOLOK, PROVINSI SUMATERA BARAT - Marlius, Erik; Novarino, Wilson; Rizaldi, Rizaldi; Ardiyanto, Asferi (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018)DO - 10.24843/metamorfosa.2018.v05.i01.p03, 2018)
This study about Malayan tapir was conducted in Supayang Kalaweit Forest from December 2015 to May 2016 using camera-trapping technique. This study aimed to know activity pattern of Malayan tapirs in Supayang Kalaweit Forest. From 129 days active-camera, 18 images consist of  two photos and 16 videos were obtained. All of images also recorded capture time of captured Malayan tapirs. Malayan tapirs was recorded at 06.00-08.00 (morning), 18.00-20.00 (evening), and 20.00-06.00 (night). No images was recorded at 08.00-18.00 (day). Based time record, activity of Malayan tapirs were nocturnal and crepuscular.